Feminisme dalam Novel Rara Mendut: Eksplorasi Perjuangan dan Pembebasan Perempuan - Hikam, Ahmad Ilzamul; Rosyidah, Dwi Ainur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study delves into the theme of feminism in the novel Rara Mendut by Y.B. Mangunwijaya. Through a descriptive qualitative approach, this research explores the struggles and liberation of women revealed in the narrative of the novel. By using the novel's text as the primary source of data, this study conducts in-depth analysis of the main female characters and situations that depict the dynamics of feminism within the Indonesian cultural context. The findings of this research can provide deeper insights into how feminism is represented and advocated for in Indonesian literary works. Keywords: Feminism, Rara Mendut, Women’s Struggle